2023
DOI: 10.1007/s44177-023-00047-3
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Urbanization, Industrialization, Natural Resources Rent, and Anthropogenic Carbon Emissions in South Asia: CS-ARDL Approach

Abstract: Rapid population growth and economic expansion affect environmental sustainability by raising emissions from increased urbanization, industrialization, and energy consumption in South Asia. Therefore, the current research aims to scrutinize the dynamic impacts of urbanization, industrialization, and energy consumption on carbon dioxide (CO 2 ) emissions in five South Asian countries (Bangladesh, Pakistan, India, Nepal, and Sri Lanka) under the umbrella of the famous stochastic regression for impact for technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Industrialization's impact on CO 2 emissions is initially positive due to its reliance on fossil fuels and high-energy-consuming manufacturing processes, as discussed in the research by Das et al [125] and Fan et al [126]. However, as industrial processes become more efficient and shift towards less energy-intensive sectors, this impact can become negative (Voumik et al [127] and Shang et al [128]). Trade, often associated with higher emissions due to increased transportation and production, also has the potential to reduce emissions through the diffusion of green technologies and practices, as demonstrated in the studies by Raihan [129], Suhrab et al [130], and Ntiamoah et al [131].…”
Section: Model (1)mentioning
confidence: 99%
“…Industrialization's impact on CO 2 emissions is initially positive due to its reliance on fossil fuels and high-energy-consuming manufacturing processes, as discussed in the research by Das et al [125] and Fan et al [126]. However, as industrial processes become more efficient and shift towards less energy-intensive sectors, this impact can become negative (Voumik et al [127] and Shang et al [128]). Trade, often associated with higher emissions due to increased transportation and production, also has the potential to reduce emissions through the diffusion of green technologies and practices, as demonstrated in the studies by Raihan [129], Suhrab et al [130], and Ntiamoah et al [131].…”
Section: Model (1)mentioning
confidence: 99%
“…Another common challenge experienced by major emerging countries is the environmental pressure stemming from the rapid growth of urbanization, which is often linked to a substantial increase in energy demands [2,17,19,45]. The research of Guloglu et al [39] revealed that as cities expanded, their load capacity factors diminished in 26 OECD countries from 1980 to 2018.…”
Section: Urbanization and Environmentmentioning
confidence: 99%
“…Carbon emissions are under intense study, revealing threats to environmental quality in developing nations like India, Mexico, Malaysia, the BRICS, and South Asian countries due to economic growth, global trade, population increase, and non-renewable resource usage [6,[15][16][17]. However, Akinsola et al [18] underline that carbon output, a significant GHG component, inadequately reflects ecological damage in both advanced and developing nations [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of moderate severity, monetary penalties are crucial. Since it utilizes preexisting tax infrastructure, carbon dioxide taxes are simpler to implement than alternative carbon pricing systems (Begum et al, 2020;Voumik et al, 2023a). They are easy to implement and promote the development and use of low-carbon technologies by all entities responsible for producing emissions (Isfat & Raihan, 2022;Voumik et al, 2023b).…”
Section: Market-based Solutionsmentioning
confidence: 99%